Dimensões históricas e socioculturais do futebol e as intensidades que o torcer proporciona - Souza, Aline da Conceição (2017)
This research has as objective discuss the intensity of football fans faced with the modernization of football, through the main fans of Sergipe soccer. With ethnographic inspiration in data construction, notions of subject and object, are put into analysis. This research was not the first experience with soccer fans, recalling the previous experience, I had the opportunity to rethink my look as a researcher at that moment, analyzing the place of knowledge-power that produces truths when assuming the position of Subject of knowledge, and this is the main effect of ethnographic inspiration. The discussion of football modernization and twisting disciplines was based on Michel Foucault's study of control and surveillance, and the intensities that the twist provides for Johan Huizinga's work on gambling as an element of culture. It was through these intensities that I realized that I had been affected by this football environment and to discuss this I used the work of Jeanne Fravet Saad about being affected.